Cellulose–xylan composite fibres as precursors for carbon fibres - Trogen, Mikaela; Kilpeläinen, Petri; Pitkänen, Leena; Sawada, Daisuke; Fliri, Lukas; Schlapp-Hackl, Inge; Hummel, Michael (Royal Society of Chemistry, 2025)
Carbon fibre reinforced composites are used to provide high-strength light-weight materials that are sought after in mobility applications to reduce weight and consequently fuel or energy consumption of the transportation vehicle. Cost and environmental considerations have resurged research on biobased precursors for carbon fibres (CFs) with cellulose being one of the most prominent examples. In this study we shed light on the purity requirements of the cellulose substrate. Thus far, most reports on lignocellulose-based CFs implement highly refined dissolving-grade pulp. To reduce the cost of the precursor fibres and their environmental footprint even further, less refined cellulose sources are desirable. The role of xylan on the properties of the precursor fibres and the carbonization behaviour of holocellulosic precursor fibres were studied. It was found that natively present hemicelluloses in paper-grade kraft pulp can be incorporated homogeneously into the cellulose matrix without impairing the fibre properties, and even showing a beneficial effect on the final carbon yield.
Keywords: carbon-fibre composites; biobased precursors; cellulose purity requirements; hemicelluloses/xylan; carbonization behaviour